Photodynamic therapy for dysplastic Barrett's oesophagus: a prospective, double blind, randomised, placebo controlled trial. Issue 5 (1st November 2000) - Ackroyd, R; Brown, N J; Davis, M F; Stephenson, T J; Marcus, S L; Stoddard, C J; Johnson, A G; Reed, M W R
Abstract : BACKGROUND AND AIMS: Photodynamic therapy (PDT) is a treatment in which cell damage is achieved by the action of light on a photosensitising agent. We have assessed the potential use of PDT in the ablation of Barrett's oesophagus. METHODS: Thirty six patients with dysplastic Barrett's oesophagus receiving acid suppression medication with omeprazole were randomised to receive oral 5-aminolaevulinic acid (ALA) 30 mg/kg or placebo, followed four hours later by laser endoscopy. Follow up endoscopy was performed at one, six, 12, and 24 months. RESULTS: Of 18 patients in the ALA group, a response was seen in 16 (median decrease in area in the treated region 30%; range 0–60%). In the placebo group, a decrease in area of 10% was observed in two patients with no change in 16 (median 0%; range 0–10%; treatment v placebo, p<0.001). No dysplasia was seen in the columnar epithelium within the treatment area of any patient in the PDT group. However, in the placebo group, persistent low grade dysplasia was found in 12 patients (p<0.001). There were no short or long term major side effects. The effects of treatment were maintained for up to 24 months. CONCLUSIONS: This is the first randomised controlled trial of PDT for Barrett's oesophagus. It demonstrates that ALA induced PDT can provide safe and effective ablation of low grade dysplastic epithelium.